Lords' Rights and Peasant Stories : Writing and the Formation of Tradition in the Later Middle Ages - Teuscher, Simon (Book collections on Project MUSE., 2012)
This book suggests rethinking master narratives about transitions from oral to literate societies, examining how village laws (Weistümer) were written down.